2019
DOI: 10.1002/ima.22383
|View full text |Cite
|
Sign up to set email alerts
|

A study on multiple array method of birdcage coils to improve the signal intensity and homogeneity in small‐animal whole‐body magnetic resonance imaging at 7 T

Abstract: Birdcage (BC) coils generate a homogeneous magnetic field (jB 1 j), whose strength depends on the length of the coils, the number of legs, the resonance frequency, the excitation method, and the length-to-diameter ratio. BC coils with a shorter distance between the end rings produce a more intense jB 1 j field with a higher level of homogeneity. Here, we propose a combination of over-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Dynamic contrast-enhanced (DCE) MR imaging 51 , 52 and susceptibility-weighted imaging (SWI) 53 , 54 , which extracts susceptibility maps from information of magnitude and phase in MR images, are techniques that can provide highly sensitive MR images from stroke and it-derived cerebral lesions, and the application of these imaging sequences can obtain more detailed information on the occurrence and recovery of brain damage. The employment of coils designed and manufactured tailored to middle animals is also a method to improve MR signal acquisition sensitivity 55 , 56 .…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic contrast-enhanced (DCE) MR imaging 51 , 52 and susceptibility-weighted imaging (SWI) 53 , 54 , which extracts susceptibility maps from information of magnitude and phase in MR images, are techniques that can provide highly sensitive MR images from stroke and it-derived cerebral lesions, and the application of these imaging sequences can obtain more detailed information on the occurrence and recovery of brain damage. The employment of coils designed and manufactured tailored to middle animals is also a method to improve MR signal acquisition sensitivity 55 , 56 .…”
Section: Resultsmentioning
confidence: 99%
“…The design concept of a modified birdcage coil for imaging chick embryos has been successfully demonstrated on a 7 T MRI scanner and has been proven to outperform the standard birdcage coil used for comparison. Whereas the SNR and \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} ${{B}_1}^ + $\end{document} homogeneity of the standard birdcage coil was shown to significantly be degraded in the area close to the end-rings [12] , [27] , [28] , the proposed coil design incorporates a curved feature which tapers down towards the end-rings in both directions, thus enhancing the transmit efficiency, the filling factor and the SNR. Here, the higher SNR was achieved with the modified coil, which has a higher filling factor and is more sample dominant (i.e., 20% higher Q-ratio shown in Table I ), despite possessing slightly higher intrinsic loss (i.e., lower unloaded Q-factor, less than a 5% difference in Table I ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SNR may diminish in areas of the embryo that are located close to the end-rings of the standard coils. While this can simply be compensated for by increasing the length of the birdcage coil, due to the filling factor the quality of the enlarged coil decreases as a function of the increased length and diameter of the coil when the size of the object is identical [12] , [26] , [27] , [28] , [29] . Moreover, maintaining consistent imaging orientations is further complicated as the position of the chick embryo changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, Nabetani et al revealed that the utilization of the shorter legs can enhance the performance of the birdcage coil for ultra-high field MRI applications [117]. Heo et al used the idea of shorter legs and devised a method for using an array of the birdcage coils in combination in order to improve the signal intensity and B1 magnetic field homogeneity at 7T [107].…”
Section: Modified Birdcage Coilsmentioning
confidence: 99%